Regulation of Embryonic Signal on Talin1 in Mouse Endometrium. (September 2019) - Shen, Ying; Qin, Aiping
Embryonic signals can affect the spatiotemporal-specific expression of the uterus to establish a successful pregnancy. Our previous study has found that talin1 underwent dynamic changes in the mouse endometrium during peri-implantation period. However, whether talin1 is affected by the embryo signals is not clear. In order to investigate the effect of embryonic signals, especially human chorionic gonadotropin (HCG) on talin1, we have designed mouse models of pseudopregnancy, delayed implantation and activation, and HCG treatment. Using these models, the expression of talin1 in the mouse endometrium was determined by immunohistochemistry and Western blotting. In the pseudopregnancy model, an increased expression of talin1 was found from day 3 to day 5, whereas the talin1 protein was decreased on day 5 in the normal pregnant mice. In the delayed implantation model, a strong cytoplasmic staining of talin1 was found, especially in stromal cells. However, after activation of the implantation, the expression of talin1 decreased ( P < .05). Furthermore, a significantly lower expression of talin1 was found at the implantation site when compared to the interimplantation sites ( P < .05). In the HCG treatment model, an intrauterine perfusion of 10u HCG significantly reduced the expression of talin1 in both stromal and epithelial cells in pseudopregnant mice ( P < .05), although further increase in the HCG concentration did not have additional effect on expression of talin1. Taken together, our data suggest that the presence of embryos can affect expression of talin1 in the mouse endometrium, and a certain concentration of HCG can regulate its expression.